Estudo radiográfico da relação entre falange distal e estojo córneo e suas possíveis correlações com obesidade e laminite em equinos da Polícia Militar do Estado de Minas Gerais - Viviana Feliciana Xavier (2012)
Obesity is a nutritional and metabolic disease more common in developed societies and each year becomes evident in the population of horses. Recent findings on the metabolic characteristics of adipose tissue are attracting attention for increasing weight gain and body fat deposits, which are able to change some important physiological functions. This study aimed to classify the body condition and their correlation with the deposition of adipose tissue in the insertion of the base of the tail and abdominal intra through ultrasound and correlate obesity and radiographic measurements of corneal case, in an attempt to to detect disorders resulting from excess weight on patrol animals Tiradentes Ensign Cavalry Regiment of the State of Minas Gerais. We evaluated 55 horses, with a mean age of 13 years in daily patrols in the region of Belo Horizonte and body score ranging from 6 to 8 points. Data were analyzed using Pearson correlation and Spearman correlations among the variables. The results indicated that the deposition of adipose tissue in the base of the tail of the insert can be used to supplement the body score ranking of horses. As for radiographic results show disagreement values in some of the indicators radiographic measurements of laminitis previously known in the literature. This study also suggests that the correlation between obesity and laminitis signal is existent in this population, but the number of obese animals were classified as insufficient. Obesity and regional adiposity represent a warning about the risk of developing the disease in horses